Perception of physicians about medical education received during their Nephrology residency - Herrera Añazco, Percy (2015)
Introduction: In Peru there are different hospitals and university programs for training of specialists in nephrology. Objective: To assess the perception of physicians who attend such programs. Methods: We carried out a descriptive cross-sectional national-level study in physicians who were in the last two years of nephrology training during February 2012 and who had graduated from it in 2010 and 2011. A self-applied questionnaire was developed along with the Peruvian Society of Nephrology based on international standards. The questionnaire evaluated: mentoring, clinical training, procedures, external rotations, research and global perception. Results: Forty doctors were surveyed nationwide. 82.5% had tutors, 22.5% of them said their support was poor. A 27.5% described their theoretical formation as deficient. The practical training was perceived as acceptable globally; however, improvements in training on peritoneal dialysis and reading kidney transplant biopsies are necessary. A 90% have national external rotations and 65% reported to have an international rotation. In the assessment of research, 77.5% thought this is deficient. In addition, 82.5% believed that residency should last four years. However, 60% reported that their residency training was good. There is a decrease in the positive perception of the aspects studied among residents regarding graduates. Conclusion: The overall perception of nephrology residency training was considered good; however, areas of tutoring, and academic and research activities on average were deficient.